Essential C♯ 2.0 - Michaelis, Mark (Addison Wesley Professional, 2006)
A new edition of this title is available, ISBN-10: 0321533925 ISBN-13: 9780321533920 " Essential C# 2.0 pulls off a very difficult task. The early chapters are comprehensible by beginning developers, while the later chapters pull no punches and provide the experienced developer with the detailed information they need to make the most of C# 2.0. Starting with the first chapter, Mark has successfully interwoven tidbits of information useful to even the most advanced developer while keeping the book approachable."--Chris Kinsman, chief architect, Vertafore, Microsoft Regional Director "How refreshing! This book deals with C# thoroughly, rather than skimming over the whole .NET framework. It is valuable to newcomers and professionals alike." -Jon Skeet, C# MVP " Essential C# 2.0 is a one-stop shop for an experienced programmer looking to ramp up on one of the hottest languages around today. Mark delivers an intelligent and detailed tour of C#, providing newcomers to the language with a solid foundation of skill on which to build their next generation of applications." -Stephen Toub, technical editor, MSDN Magazine "This book provides complete, up-to-date coverage of all the programming constructs in C#. Masterfully organized, it allows beginning programmers to get on board and leads more experienced programmers into the world of structured programming. Because of its unwavering focus on the essential programming constructs of C#-such as generics, delegates, and much more-this book is indispensable. For programmers who want to solve their day-to-day programming issues using the latest features this modern programming language has to offer, this book is indispensable." -Narendra Poflee, IT integration specialist, Itron Inc." Essential C# 2.0 is an ideal book for all programmers interested in C#. If you are a beginner, you will quickly learn the basics of C# programming and become familiar with the concepts. The flow of the text is easy to follow and does a great job of not repeating concepts that have already been covered. For the experienced programmer, this book has priceless nuggets embedded within its pages, making it a great read for programmers who are already familiar with C#. This will be a book that I will keep next to my computer for years to come." -Michael Stokesbary, software engineer, Itron Incorporated Essential C# 2.0 is a clear, concise guide to C#-including the features new to C# 2.0. The book clearly presents material for beginn ...
Print version record
Keywords: C# (Computer program language); C# (Langage de programmation); C♯ (Computer program language)